MANAJEMEN KEPEMIMPINAN PADA LEMBAGA PENDIDIKAN ISLAM - Husaini, Husaini; Fitria, Happy (Graduate Program Magister Manajemen Pendidikan, 2019)
Success a management cannot be separated from management principles which formed the basis and the value of the management itself. Principles in management should be resilient, it needs to be considered in accordance with the special conditions and situational change. The general notion of management is an activity to achieve the goals that have been determined (getting things done through the effort of other people). Effective leadership is based on those they lead (conditions and situations). The leadership in Islamic educational institutions will be very effective in accordance with the conditions and situations that arise at the time. There is no effective leadership style but with the situation and the growing conditions. In the management of Islamic educational institutions must have some component of the right to produce a proper and prudent performance include planning, organizing, actuating, dan controlling.